THE IMPACT OF TRADE ACCOUNT DEFICIT ON UNEMPLOYMENT SCENARIO: AN EMPIRICAL STUDY ON JORDAN DURING THE PERIOD OF 2000-2012 - Al-Sawai'e, Khaled Mohammed; Abdul A'aL, Shereen (European Scientific Journal, ESJ, 2015)
The aim of this paper is to study the short-term causal relationship between unemployment and the volume of trade deficit in jordan for the period 2000:01 – 2012:02. This study provides evidence of the absence of a long-term relationship between the two variables. We use granger causality test and propose an augmented dickey-fuller (adf) coefficient test for detecting the presence of a unit root in the model. The results show that trade account deficit causes unemployment, and unemployment causes the trade account deficit in the short run. This indicates that trade liberalization is also able to increase imports, decrease aggregate productivity in the differentiated sectors, and create inefficiency on economic performance. Thus, this would simultaneously decrease employment opportunities for jordan’s labour force. Trade account can also be an additional negative effect in increasing jordanian’s unemployment scenario in the future.